Journal of Intelligent Systems (De Gruyter, 1991)
The journal provides a compilation of stimulating and up-to-date articles within the field of intelligent systems. The focus of the journal is on high quality research that addresses paradigms, development, applications and implications. The list of topics spans all the areas of modern intelligent systems. JISYS publishes research papers, reviews as well as short research communications, essays, and book reviews.